An inter‐species protein–protein interaction network across vast evolutionary distance. Issue 4 (23rd April 2016) - Zhong, Quan; Pevzner, Samuel J; Hao, Tong; Wang, Yang; Mosca, Roberto; Menche, Jörg; Taipale, Mikko; Taşan, Murat; Fan, Changyu; Yang, Xinping; Haley, Patrick; Murray, Ryan R; et al.
Abstract: In cellular systems, biophysical interactions between macromolecules underlie a complex web of functional interactions. How biophysical and functional networks are coordinated, whether all biophysical interactions correspond to functional interactions, and how such biophysical‐versus‐functional network coordination is shaped by evolutionary forces are all largely unanswered questions. Here, we investigate these questions using an "inter‐interactome" approach. We systematically probed the yeast and human proteomes for interactions between proteins from these two species and functionally characterized the resulting inter‐interactome network. After a billion years of evolutionary divergence, the yeast and human proteomes are still capable of forming a biophysical network with properties that resemble those of intra‐species networks. Although substantially reduced relative to intra‐species networks, the levels of functional overlap in the yeast–human inter‐interactome network uncover significant remnants of co‐functionality widely preserved in the two proteomes beyond human–yeast homologs. Our data support evolutionary selection against biophysical interactions between proteins with little or no co‐functionality. Such non‐functional interactions, however, represent a reservoir from which nascent functional interactions may arise. Synopsis: An inter‐species "inter‐interactome" was generated by systematic mapping protein–protein interactions between human and yeast proteomes. Comparisons of the inter‐species interactome with the two "parent" intra‐species human and yeast networks reveal evolutionary constraints and plasticity of biological systems. The human and yeast proteomes widely retain the ability to form inter‐species protein–protein interactions. Inter‐species interactions significantly but not exclusively correspond to ancestral binding properties preserved in human and yeast proteins. Ancestral binding properties appear to underlie conserved and species‐specific functions. Abstract : An inter‐species "inter‐interactome" was generated by systematic mapping protein–protein interactions between human and yeast proteomes. Comparisons of the inter‐species interactome with the two "parent" intra‐species human and yeast networks reveal evolutionary constraints and plasticity of biological systems.